2018
DOI: 10.1007/s00253-018-9021-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid development of stable transgene CHO cell lines by CRISPR/Cas9-mediated site-specific integration into C12orf35

Abstract: Chinese hamster ovary (CHO) cells are the most widely used mammalian hosts for recombinant protein production. However, by conventional random integration strategy, development of a high-expressing and stable recombinant CHO cell line has always been a difficult task due to the heterogenic insertion and its caused requirement of multiple rounds of selection. Site-specific integration of transgenes into CHO hot spots is an ideal strategy to overcome these challenges since it can generate isogenic cell lines wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 36 publications
3
35
1
Order By: Relevance
“…They found that C12orf35 locus (a telomeric region of chromosome 8) [ 34 ] was the most advantageous among these three genes. [ 35 ] T site of ywhae gene that we found in this study is the potential genome hotspot to construct cell lines for recombinant protein production. Further study will be needed for this information.…”
Section: Discussionmentioning
confidence: 87%
“…They found that C12orf35 locus (a telomeric region of chromosome 8) [ 34 ] was the most advantageous among these three genes. [ 35 ] T site of ywhae gene that we found in this study is the potential genome hotspot to construct cell lines for recombinant protein production. Further study will be needed for this information.…”
Section: Discussionmentioning
confidence: 87%
“…In prior works, the use of HDR-mediated SSI with linear donor DNA, sometimes referred to as homology-mediated end joining (HMEJ), was accomplished via nuclease-mediated cleavage and release of circular plasmids in vivo [21,37,50,51]. Nonetheless, we observed a 2.3fold improvement in SSI efficiency when using a PCR-amplified linear HDR donor compared with a plasmid HDR donor (both with similar homology arm lengths), which matches previously documented efficiency gains when comparing the two donor formats [21,50,51]. Together, our findings show the functionality of the reporter system and promote the use of linearized HDR donors to improve SSI efficiency relative to other DSB repair strategies.…”
Section: Comparison Of Repair Pathways For Ssi: Hdr Is Most Efficientmentioning
confidence: 99%
“…Direct silencing of the CMV promoter used for most transgenes, either by DNA-methylation or by changes in the histone modifications has also been shown [197][198][199][200]. These different strategies to silence the gene of interest are most likely due to the cell's drive to remove the stress of high productivity [201][202][203], by which ever means possible. Therefore, a frequent cause of loss of productivity is also the complete deletion of the recombinant genes from the genome [204,205].…”
Section: Maintaining Stabilitymentioning
confidence: 99%